(untitled) (Journal of the College of Basic Education, 2022)
Strategic management is the process that includes a set of steps through which the management analyzes the strengths and weaknesses of the organization and the capabilities available to it and draws up policies that lead to achieving the goals in light of the external threats to the organization through taking long and short-term decisions according to what the management deems... whereby decisions are taken Decisions through the process of evaluation, data collection and analysis, then choosing the best alternatives, and that requires a high degree of efficiency, then starting the process of implementing these decisions after preparing the material and human capabilities and moving these capabilities in an organized and orderly manner, then comes the evaluation stage